Moses Maimonides: Biographic Outlines - Fred Rosner (Rambam Maimonides Medical Journal, 2010)
Moses, son of Maimon (Rambam in Hebrew, Abu Imran Musa Ibn Maimun in Arabic), was born in Cordova, Spain on 30 March 1135, corresponding to Passover eve of the Hebrew year 4895. His mother died in childbirth, and consequently his father Dayan (judge) Maimon raised him. Persecution by the Almochades, a fanatical group from North Africa, forced the Maimon family to flee Cordova in the year 1148. Maimonides was 13 years old. The family wandered through southern Spain and northern Africa for the next 10 years and finally settled in Fez, Morocco in 1158.